ANALISIS TERHADAP PERLUNYA PENYESUAIAN LAPORAN KEUANGAN HISTORIS (CONVENTIONAL ACCOUNTING) MENJADI BERDASARKAN TINGKAT HARGA UMUM (GENERAL PRICE LEVEL ACCOUNTING) - Puteri Qurrotul Akyun (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This study aims to determine the Need for Adjustment Analysis of Historical Financial Statements (Conventional Accounting) be based on the General Price Level (General Price Level Accounting). The population in this study is LQ45 company listed on the Indonesia Stock Exchange (BEI) in 2013-2015. While the sample is a company incorporated in LQ45 index. The sampling technique was conducted by purposive sampling method. Samples are 4 companies with three years of observation. So the total sample studied was 12 companies. The data used is secondary data drawn through technical documentation, that annual report of companies LQ45 years 2013-2015. The data were analyzed using the Wilcoxon test. The results of this study indicate that (1) There is no significant difference between the average financial ratios based on the historical with the average financial ratios based on the general price level (2) there is a significant difference between the average financial ratios based on the historical average -rata financial ratios based on the general price level.